Do Employee Interests Affect Target Board Decisions About Acquisition Offers? Evidence from Changes in Unemployment Insurance - Guo, Lixiong; Kong, Jing; Masulis, Ronald W. (Management Science, 2024)
We explore whether employee interests affect the evaluation of acquisition offers by target boards of directors. Exploiting changes in state unemployment insurance (UI) as sources of exogenous variation in worker unemployment costs, we find that lower unemployment costs increase acquisition activity. The adoption of state constituency statutes strengthens this relation. Boards of target firms having high labor intensity, low short-term institutional ownership, headquartered in low population or high social capital counties, and with female independent directors, more often strongly weight employee interests. Higher UI levels are also associated with larger postacquisition layoffs. Our evidence supports theories rationalizing target boards’ consideration of employee interests. This paper was accepted by Victoria Ivashina, finance. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2022.01379 .